El acoso escolar y la autoestima - Quilligana Cevallos, Vilma Elizabeth (2017)
The propose of this study was to determine the current situation of school bullying by observing and recording data in order to improve the self-esteem of the students of the Baccalaureate of the Mulaló Educational Unit of the Latacunga canton of Cotopaxi Province. The premise that generated the present study was to determine through the investigation the incidence of school bullying in the self-esteem of the students of the institution under study. During the execution of the research process, the categories of the research were described in a detailed way from the theoretical approach taking into account the fundamental concepts of each of the variables of the problem. Data collection techniques and instruments were used to collect data to determine the factors that affect school bullying and self-esteem of the 143 students of the Mulaló Educational Unit in the academic year 2016-201. Finally the data obtained in the research for the elaboration of conclusions and recommendations were analyzed. All this process allowed to suggest actions for managers and teachers to make decisions regarding this problem and improve interrelationships and social coexistence among students.